2007
DOI: 10.1109/tip.2007.906256
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity and Morphological Diversity in Blind Source Separation

Abstract: Over the last few years, the development of multichannel sensors motivated interest in methods for the coherent processing of multivariate data. Some specific issues have already been addressed as testified by the wide literature on the so-caIled blind source separation (BSS) problem. In this context, as clearly emphasized by previous work, it is fundamental that the sources to be retrieved present some quantitatively measurable diversity. Recently, sparsity and morphological diversity have emergedas a novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
161
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 30 publications
0
161
0
Order By: Relevance
“…We use GMCA (Bobin et al 2007a(Bobin et al , 2007b(Bobin et al , 2007c(Bobin et al , 2008, specifically tailored to foreground removal (Chapman et al 2013), to remove the dominant modes from the data cubes in Stokes I and any remaining instrumental polarization leakage in Stokes V.…”
Section: Generalized Morphological Component Analysismentioning
confidence: 99%
“…We use GMCA (Bobin et al 2007a(Bobin et al , 2007b(Bobin et al , 2007c(Bobin et al , 2008, specifically tailored to foreground removal (Chapman et al 2013), to remove the dominant modes from the data cubes in Stokes I and any remaining instrumental polarization leakage in Stokes V.…”
Section: Generalized Morphological Component Analysismentioning
confidence: 99%
“…In Bobin et al (2007), it was shown that sparsity enhances the diversity between the components thus improving the separation quality. The spectral signatures of CMB and SZ are assumed to be known.…”
Section: A3 Generalised Morphological Component Analysis (Gmca)mentioning
confidence: 99%
“…it is actually part of n. We can expand the data x in a PoS(AASKA14)005 CD/EoR Foreground Removal Emma Chapman wavelet basis and seek an unmixing scheme, through the estimation of A, which yields the sparsest components s in the wavelet domain. For more technical details about GMCA, we refer the interested reader to Bobin et al (2007Bobin et al ( , 2008aBobin et al ( ,b, 2013, where it is shown that sparsity, as used in GMCA, allows for a more precise estimation of the mixing matrix A and more robustness to noise than ICA-based techniques such as FastICA. For a previous application of GMCA to EoR data see Chapman et al (2013).…”
Section: Gmcamentioning
confidence: 99%